DESAIN PEMBELAJARAN STATISTIK MELALUI GOOGLE CLASSROOM - Chairul Fajar Tafrilyanto; Harfin Lanya; Moh. Zayyadi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2020)
This study aims to design statisticl learning through the use of Google Classroom. In this study, a valid learning device was produced (validated by experts), and received a positive response as well as design learning statistic l. This research is classified as qualitative research. The 11th semester students at the University of Madura who are taking this 1st statistics course are the subjects in this study. While the data collection technique used is to use a response sheet that is filled out via Google Form and an assignment in the Google Classroom . The data analysis technique used is that student learning outcomes are sought for the average value if the result is more than 75, then the learning design applied is successful and can be used for other courses, and the response to learning outcomes is said to be positive if it gets a percentage of more than 75%. The observation sheet is filled with attention to student activities during the work of assignments and assignments are sent online to students via Google Classroom media. Problem assignments are given to students after they have studied statistics 1. The learning tools designed in this study are in the form of RPM, and test questions. Through this learning design, valid, effective and practical learning tools are obtained.